THE ROLE OF UNIVERSITIES IN ENSURING THE HUMAN RESOURCES OF THE VOLGOGRAD REGION - Vladimir I. Petrov; Victor B. Mandrikov; Tamara S. D’Yachenko (Высшее образование в России)
The article touches the issues of employment of graduates of educational institutions of Volgograd region. The authors analyze the contingent of students and faculty members of universities and university branches, activities of their centers to promote the employment of graduates. The results of monitoring of the regional labor market and skill( mix issue experts over the past 5 years.